A survey of thrombosis experts evaluating practices and opinions regarding venous thromboprophylaxis in patients with active cancer hospitalized with an acute medical illness - Moretto, Patricia; Park, Junghyun; Rodger, Marc; Le Gal, Grégoire; Carrier, Marc (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Current clinical practice guidelines recommend the use of prophylactic doses of low molecular weight heparins for cancer patients requiring hospitalization for acute medical illness. However, a recently published meta-analysis suggested that the risk-benefit ratio of current thromboprophylaxis regimens administered to all cancer patients admitted for medical illness is unclear. We sought to assess the clinical equipoise in using thromboprophylaxis for hospitalized medically ill cancer patients. Methods An electronic survey was conducted. The target sample included Thrombosis experts and members of Thrombosis Canada or the VECTOR research group. Results The survey was distributed 54 participants. The final response rate was 67% (36/54). The majority (75%; 95% CI: 60.3 to 85%) of responders indicated that the benefits of pharmacological parenteral thromboprophylaxis outweigh the risks. However, 63.9% (95% CI: 50.6 to 77.3%) believe that there is still clinical equipoise around the use of thromboprophylaxis in this patient population, and 88.9% (95% CI: 77.3 to 95.8%) would consider participating in a randomized trial—30.6% and 58.3% in a placebo-controlled or comparison of different agents/dosing-controlled randomized trial, respectively. For participants who would consider a randomized-controlled trial comparing different doses of thromboprophylaxis agents, the MCID was 2% between the two arms. The most common drug to be compared was enoxaparin (26%), and the two suggested doses were 30 mg and 40 mg SC twice daily. Conclusions Our clinical survey of thrombosis experts confirms that there is equipoise regarding the use of current regimens of parenteral pharmacological thromboprophylaxis in medically ill cancer patients. A majority of physicians would participate in a randomized-controlled trial comparing different dose of LMWH. The MCID in the risk of VTE identified was 2%.